2013
DOI: 10.1371/journal.pone.0083816
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Fragile Gains: The Need to Maintain Coverage with Long-Lasting Insecticidal Nets for Malaria Control and Likely Implications of Not Doing So

Abstract: Global commitment to malaria control has greatly increased over the last decade. Long-lasting insecticidal nets (LLINs) have become a core intervention of national malaria control strategies and over 450 million nets were distributed in sub-Saharan Africa between 2008 and 2012. Despite the impressive gains made as a result of increased investment in to malaria control, such gains remain fragile. Existing funding commitments for LLINs in the pipeline to 2016 were collated for 40 sub-Saharan African countries. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Notwithstanding, funding for malaria control peaked at $US2 billion in 2011 [43] and has begun to decline, ushering in an era of limited resources. Amidst the push to achieve universal coverage and dwindling resources, there is the potential danger whereby “keep-up” strategies lose resources and funding to its more attractive “catch-up” counterpart.…”
Section: Recent Policy and Funding For Llins Among Key Donors And Parmentioning
confidence: 99%
“…Notwithstanding, funding for malaria control peaked at $US2 billion in 2011 [43] and has begun to decline, ushering in an era of limited resources. Amidst the push to achieve universal coverage and dwindling resources, there is the potential danger whereby “keep-up” strategies lose resources and funding to its more attractive “catch-up” counterpart.…”
Section: Recent Policy and Funding For Llins Among Key Donors And Parmentioning
confidence: 99%
“…Eleven scenarios are considered that span a range of baseline ITN coverage values and EIR values. Although spatial targeting should cause these two quantities to be positively correlated in practice, the large funding gap in ITNs [ 10 ] suggests that the only coverage-EIR combination considered here that may be rare in practice is the 80 % coverage, EIR = 10 scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Although ITNs are effective at preventing malaria [ 6 ], demand is highly price-sensitive and is greatly reduced when ITNs are not free [ 7 , 8 ], making them attractive candidates for free targeted intervention. The World Health Organization recommended a switch from targeted ITN intervention (e.g., for children under five and pregnant women) to universal ITN coverage in 2008 [ 9 ], which led to the distribution of over 450M ITNs in sub-Saharan Africa between 2008 and 2012 [ 10 ]. Nonethless, malaria control funding peaked in 2012 and has begun to decline, with funding commitments in 2013–2016 estimated to meet just over half of demand, yielding a funding gap of 374M ITNs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mass distributions are a cost-effective way to quickly achieve high coverage over a particular area, coverage gaps begin to appear almost immediately postdistribution through net deterioration, loss of nets, and population growth, therefore, requiring complementary continuous distribution channels to sustain or "keep up" coverage over time [8,[26][27][28]. Models have suggested that relying solely on mass distributions without keeping up access through health facility-based systemsthrough ANC and EPI (sometimes also called "routine distribution") would result in lower levels of access [29].…”
mentioning
confidence: 99%